Hubungan efikasi diri dengan tingkat kepatuhan pengobatan antiretroviral terapi pada laki-laki seropositif HIV - vincenkogopa; Priyantari, Wiwin; Rosyad, Yafi Sabila (Infomasi dan Promosi Kesehatan, 2022)
Background: Compliance with ART treatment is an important indication to improve the quality of life of people dliving with HIV / AIDS (PLWHA), prevent drug resistance, and reduce mortality. One factor that can influence the level of adherence to ART treatment is the self-efficacy of ARV treatment levels.Objectives: To determine the relationship of self-efficacy with adherence to taking medication in men with HIV / AIDS at Victoria Plus Foundation Yogyakarta. Methods: This research is a quantitative correlation with cross sectional approach. The research sample of 35 respondents was determined by probability sampling technique. The research instrument was in the form of a self-efficacy questionnaire and medication adherence. Data analysis techniques using the Kendall Tau test. Results: Self-efficacy in people with HIV / AIDS was in the confident category of 97.1%. Treatment adherence in people with HIV / AIDS is in the category of non-compliance by 80.0%. There is a relationship between self-efficacy and medication adherence in male patients with HIV / AIDS based on pvalue = 0.023. Conclusion: There is a relationship between self-efficacy and medication adherence in male patients with HIV / AIDS at the Victori Plus Foundation in Yogyakarta.